Epidemiology and Risk Factors for Multiple Sclerosis: A Narrative Review of Recent Evidence - Alrouwab, Osamah; Eldaouki, Husam; Amara, Issa (Khalij-Libya Journal of Dental and Medical Research, 2026)
One of the main causes of non-traumatic neurological disability in young adults worldwide is multiple sclerosis (MS), a chronic immune-mediated demyelinating and neurodegenerative disorder of the central nervous system (CNS). Increasing absolute prevalence is seen in recent epidemiological trends from 2021 to 2025, while age-standardized rates are stabilizing due to improved diagnostics, survival, and demographic shifts. The current narrative review's objective is to examine high-caliber studies conducted globally between 2021 and 2025 that address the epidemiology, burden, and different risk factors related to multiple sclerosis (MS), with an emphasis on the effects of age, gender, ethnicity, and other interacting factors. Key Findings: Global prevalence of ~1.89 million cases in 2021 (age-standardized rate: 23.9 per 100,000), with ~62,000 new cases each year; female-to-male ratio of ~3:1. DALYs are up by 43% from 1990, but with a trend downward for age-standardized rates with advances in management. Incidence is framed by disparities with higher rates for Whites (77% of the U.S.) than Black (10%), followed by Hispanic (7%) cases, and also high levels of radiological severity, handicap, and poor outcomes for ethnic minorities of these groups. Age of peak incidence progresses to older groups for individuals aged 20-40 years. Genetic underpinnings with large effects (e.g., HLA-DRB1*15:01 for ~48% of heritability), strong susceptibility to Epstein-Barr virus infection (near ubiquity at onset; 32-fold increase for molecular mimicry), vitamin D deficiency, smoking, obesity, and altered gut microbiomes are environmental components of risk. Incidence is seen to decline modestly for age-standardized incidence rates, mortality rates, and DALYs through 2035. From this review, the emphasis on MS as a partially preventable disease falls within the context of a rising absolute prevalence and existing inequities in the field. Future complementary strategies should therefore encompass a wide range of populations as well as risk modification measures such as EBV-related therapies and smoking cessation.